2016
DOI: 10.1080/14616688.2016.1196239
|View full text |Cite
|
Sign up to set email alerts
|

Political trust and residents’ support for alternative and mass tourism: an improved structural model

Abstract: Political trust is a key requirement for tourism policies to flourish and sustain. The purpose of the research was to investigate the determinants of political trust and analyze whether the latter influences residents' support for mass and alternative tourism. To this end, we develop a structural model based on the social exchange theory, institutional theory of political trust, and cultural theory of political trust. The model proposes six determinants of political trust which in turn is considered to influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 93 publications
5
42
1
3
Order By: Relevance
“…[ Table 5 near here] Hypothesis 1 which proposed a direct positive relationship between perceived benefits and ORS was supported by Gursoy and Kendall's (2006) study as well as in the SHC and MHC contexts. These results confirm those of several studies that found perceived benefits to be among the strongest determinants of residents' support for mega-events and other tourism related development (Gursoy & Rutheford, 2004;Nunkoo & Gursoy, 2017;Nunkoo & Ramkissoon, 2011a, 2011b. The findings also confirm the postulates of the SET, suggesting that individuals are likely to engage in an exchange (i.e.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[ Table 5 near here] Hypothesis 1 which proposed a direct positive relationship between perceived benefits and ORS was supported by Gursoy and Kendall's (2006) study as well as in the SHC and MHC contexts. These results confirm those of several studies that found perceived benefits to be among the strongest determinants of residents' support for mega-events and other tourism related development (Gursoy & Rutheford, 2004;Nunkoo & Gursoy, 2017;Nunkoo & Ramkissoon, 2011a, 2011b. The findings also confirm the postulates of the SET, suggesting that individuals are likely to engage in an exchange (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…While the significant inverse relationship noted in the SHC is consistent with the postulate of SET and a number of empirical findings (e.g. Nunkoo & Gursoy, 2017;Nunkoo & Ramkissoon, 2011a), the result of the hypothesis in the MHC contradicts the SET. This may be because in a MHC perceived costs may be diffused as residents may develop a "shared-cost" perception and/or perceive less risk (i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Understanding the local community perspective in the planning phase of development projects has been shown to significantly minimise negative impacts, maximise positive impacts and leads to greater support for those projects (Nunkoo & Gursoy, 2017;Stylidis et al, 2017;Stylidis, 2018). One way to assess the nature and degree of the costs and benefits is to seek the perspective of local residents in these remote communities.…”
Section: Advantages and Disadvantages Of Tourism Developmentmentioning
confidence: 99%
“…One way to assess the nature and degree of the costs and benefits is to seek the perspective of local residents in these remote communities. Understanding the local community perspective in the planning phase of development projects has been shown to significantly minimise negative impacts, maximise positive impacts and leads to greater support for those projects (Nunkoo & Gursoy, 2017;Stylidis et al, 2017;Stylidis, 2018).…”
Section: Advantages and Disadvantages Of Tourism Developmentmentioning
confidence: 99%
“…Uma forma homogênea, rígida e padronizada, similar ao sistema fordista de manufatura (Nunkoo;Gursoy, 2017). A rápida e abundante geração de receitas e postos de trabalho torna-se mais relevante, porém "não há dúvidas de que a forma como o turismo utiliza o meio ambiente hoje terá consequências para o seu uso -e talvez até para sua viabilidade -no futuro" (Lickorish e Jenkins, 2000, p. 116).…”
Section: Turismo Massificação E Impactosunclassified